- #1

- 18

- 0

Hi!

Why is a in F=m*a

equal to a =(d^2 x) / (d t )^2 and not to (d x)^2 / (d t )^2

Mark

Why is a in F=m*a

equal to a =(d^2 x) / (d t )^2 and not to (d x)^2 / (d t )^2

Mark

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Mark1991
- Start date

- #1

- 18

- 0

Hi!

Why is a in F=m*a

equal to a =(d^2 x) / (d t )^2 and not to (d x)^2 / (d t )^2

Mark

Why is a in F=m*a

equal to a =(d^2 x) / (d t )^2 and not to (d x)^2 / (d t )^2

Mark

- #2

- 15,415

- 686

The second derivative is

[tex]a = \frac {dv}{dt} = \frac{d}{dt}(v) = \frac d {dt} \left( \frac {dx}{dt} \right) = \frac d {dt} \left( \frac {d}{dt} (x)\right)[/tex]

Note that if we treated this is a fraction (which it isn't), one could write

[tex]a = \frac {dd}{(dt)(dt)}(x) = \frac {d^2}{(dt)^2}(x)[/tex]

Share: